2014
DOI: 10.1158/1541-7786.mcr-13-0281
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-Binding Complex Recruits HDAC1 to Repress Bcl-2 Transcription in Human Ovarian Cancer Cells

Abstract: Elevated expression of the anti-apoptotic factor Bcl-2 is believed to be one of the contributing factors to an increased relapse rate associated with multiple cisplatin-resistant cancers. DNA damage-binding protein complex subunit 2 (DDB2) has recently been revealed to play an important role in sensitizing human ovarian cancer cells to cisplatin-induced apoptosis through the down-regulation of Bcl-2, but the underlying molecular mechanism remains poorly defined. Here, we report that DDB2 functions as a transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…3A). These results confirmed our previous observations and indicated that DDB2 physically interacts with HDAC1 [38]. We further investigated whether DDB2 affects translocation of HDAC1 to chromatin.…”
Section: Resultssupporting
confidence: 91%
“…3A). These results confirmed our previous observations and indicated that DDB2 physically interacts with HDAC1 [38]. We further investigated whether DDB2 affects translocation of HDAC1 to chromatin.…”
Section: Resultssupporting
confidence: 91%
“…DDB2 expression lentiviruses were generated as described before (21). To establish shDDB2 stably transfected cell lines, MISSION shDDB2 (TRCN0000083993) plasmids (Sigma) were transfected into 2008 cells using eletroporation.…”
Section: Methodsmentioning
confidence: 99%
“…The low expression of DDB2 in cisplatin-resistant ovarian cancer cell lines (18) and high-grade colon cancer (19) and skin cancer (20) indicates a link between DDB2 expression and tumor progression. Recently, new functions of DDB2 beyond its role in DNA repair have been identified, e.g., inhibiting cellular apoptosis through downregulation of Bcl-2 (18, 21) and p21 (22), suppressing colon tumor metastasis through blocking epithelial–mesenchymal transition (EMT; ref. 19), and limiting the motility and invasiveness of invasive human breast tumor cells by regulating NF-κB activity (23), as well as mediating premature senescence (24).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have revealed the role of DDB2 in mediating the sensitivity of ovarian cancer cells to cisplatin [12, 13]. As a DNA damage binding protein, DDB2 is involved in the repair of UV-induced CPD by the NER pathway, but is not required for the repair of cisplatin-induced intrastrand crosslinks.…”
Section: Resultsmentioning
confidence: 99%